2019
DOI: 10.3390/cells8121559
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Inheritance of Environmentally Induced Epigenetic Alterations during Mammalian Development

Abstract: Genetic studies traditionally focus on DNA as the molecule that passes information on from parents to their offspring. Changes in the DNA code alter heritable information and can more or less severely affect the progeny’s phenotype. While the idea that information can be inherited between generations independently of the DNA’s nucleotide sequence is not new, the outcome of recent studies provides a mechanistic foundation for the concept. In this review, we attempt to summarize our current knowledge about the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 199 publications
(209 reference statements)
0
54
0
Order By: Relevance
“…It is well known that cancer is a multistage genetic and epigenetic disease with a complex etiology involving mutation, upregulation, downregulation, and deletion of oncogenes and tumor suppressor genes [1][2][3][4]. Gene amplification/deletion/mutation or chromosomal translocation is abnormal genetic changes that lead to tumorigenesis and tumor development [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that cancer is a multistage genetic and epigenetic disease with a complex etiology involving mutation, upregulation, downregulation, and deletion of oncogenes and tumor suppressor genes [1][2][3][4]. Gene amplification/deletion/mutation or chromosomal translocation is abnormal genetic changes that lead to tumorigenesis and tumor development [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some studies suggest that epigenetic changes could be involved in transgenerational inheritance; i.e., epigenetic patterns may be inherited by the progeny. For example, chemically modified DNA or the chromatin of reproductive cells contribute to the expression of a single allele in the progeny, which is called "the phenomenon of genome staining" (or "genomic imprinting") [61][62][63][64][65]. Genomic imprinting represents yet another example of non-Mendelian inheritance, which could be called "heretic inheritance" [66].…”
Section: Non-mendelian "Heretic" Transgeneration Inheritance Of Epigmentioning
confidence: 99%
“…Recent data indicate that the profile of epigenetic changes in patients suffering from AD differs from that seen in healthy individuals. This applies to the genes affecting the regulation of immune response and inflammatory processes, e.g., the inhibition of responses dependent on Th1 lymphocytes, and the promotion of the Th2 bias, as well as the genes involved in innate immunity and those encoding the structural proteins of the epidermis [7,8,13,14,40,[61][62][63][64][65][66]. In the skin, it has been shown that DNA methylation profiles also differ in the epidermis of AD patients in comparison to those in healthy people; specifically, this involves genes of known structural and antimicrobial function, i.e., S100 or keratin genes (Table 3).…”
Section: Epigenetic Changes In Atopic Dermatitismentioning
confidence: 99%
“…Evidence accumulated across animal and plant research over the last 20 years has confirmed that the inherited determinants of an organism's phenotype are more than just DNA (Cavalli and Heard, 2019). Inheritance of RNA, protein and metabolites in the male or female gamete can influence a variety of traits such as size, shape, behaviour and health (Legoff et al, 2019;Perez and Lehner, 2019). Furthermore, the levels and types of inherited molecules can be influenced by ancestral environmental exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Ancestral environmental changes that have been found to alter phenotypes of descendants include behavioural stress, toxin exposure and nutritional variation (Cavalli and Heard, 2019;Legoff et al, 2019;Perez and Lehner, 2019). The latter is perhaps the most-studied, and examples of ancestral diet altering descendent phenotype have been documented due to overor under-nutrition in natural populations including human (Aiken and Ozanne, 2014) and laboratory organisms such as Caenorhabditis elegans (Kishimoto et al, 2017;Tauffenberger and Parker, 2014), Drosophila (Emborski and Mikheyev, 2019;Ost et al, 2014;Strilbytska et al, 2020;Vijendravarma et al, 2010;Xia et al, 2016) and rodents (Aiken and Ozanne, 2014).…”
Section: Introductionmentioning
confidence: 99%